ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA SMP DALAM MENYELESAIKAN SOAL PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL - Siti Nuryatin; Luvy Sylviana Zanthy (Journal on Education, 2019)
This research is a descriptive qualitative study that aims to analyze the percentage of mathematical connection abilities in solving questions of One Variable Linear Equations and Inequalities which are seen based on indicators. The subjects of this study were seventh grade students of SMP in one of the cities of Cimahi which consisted of 22 students. The instrument used is a description test in the form of pretest and posttest conducted before the first cycle and after the second cycle. Students 'mathematical connection ability is seen based on the indicators on the pretest and posttest there are differences so that it can be said that students' mathematical connection skills are better than their previous abilities. The highest mathematical connection ability of students in the pretest test is found in the first indicator, namely using the relationship between mathematical topics with a percentage of 74% while the high indicator of posttest tests on indicator three is using Mathematics in everyday life with a percentage of 81%. There is also the lowest connection ability at the pretest found in the fourth indicator, which is to understand the equivalent representation of the same concept with a percentage of 5% while the low posttest indicator on the second indicator is using mathematics in other subjects with a percentage of 47%. So that the mathematical connection ability can be said to be better than before in solving equation problems and one variable linear inequality.